DE Garengeot Hernia - Farhan Shahzad, Muhammad Azam Arif, Adeel Ali Tahir, Mr Amir Siddiqui (Pakistan Journal of Medical & Health Sciences, 2022)
Croissant de Garengeot’s hernia is a rare condition and occurs mostly in females. The presence of an appendix in a femoral hernia is uncommon, and the presence of appendicitis is even more infrequent. The presence of appendix in femoral hernias as an incidental finding occurs in about 0.9%, and the incidence of appendicitis is 0.08%-0.13%. A 49 year old woman presented in the emergency department with an acutely painful lump in her right groin. Examination revealed a non-reducible, tender right femoral hernia with redness of the overlying skin. Intra-operative findings were a femoral hernia sac containing appendix with strangulation of its distal third. Appendicectomy and repair of the femoral hernia were done and patient made an uneventful recovery and discharged home on the 3rd postoperative day.